Identidade, diáspora, exílio : um estudo sobre o intelectual pós-colonial - Silva, Carmem Emanuela Santos (2018)
This paper focuses on the impacts of globalization and the so-called late modernity on cultural identities and, consequently, on intellectual activity. A brief diagnosis of modernity, the characteristics of globalization and the emergence of heterogeneous identities is presented, whose unifying project was a construction. Our goal is to map, in the context of modernity, how the intellectual appropriates the results of decolonization and the emergence of diasporic identities for the conduct of his work by suspending certain nationalist ideals. The old European nations created their national identities from a homogenizing imperative of excluding differences in the name of an ontological security. The post-war world was particularly marked by the independence of many former colonies and the foreigner, whose difference was captured in the old unifying project, reappears as the protagonist of tensions in the old well-resolved identities until then. The diasporic movement (real and metaphorical) of individuals in exile will serve as a model for the intellectual, inserted in games of power that call it to conform to discourses of domination, to create fissures, precisely, in the mismanagement of power. In order to address these issues, the study was divided into a few chapters. The first of these represented a retreat to questions pertinent to the changes in the meanings of cultural identity in late modernity through, summarily, Stuart Hall's analysis and the view of Cultural Studies. The second is to explore some of the paths briefly described in the previous chapter from the presentation of national elements as constructions: the nation, the imagined community and the invented tradition, as well as, in this context, the defense of the diaspora as a subversion of homogeneous national models. The third focuses on the problematic of the intellectual practice of the one who takes the exile as a destiny, through the analyses of Edward Said and Gayatri Spivak. At the limit, at the time of the diaspora, the intellectual is summoned to assume a position not submitted to power and to provoke, like the foreigner in the stability of nations, grooves on the frontiers of domination.